Exercises in psychological testing and assessment - Cohen, Ronald Jay. (Boston McGraw-Hill Higher Education, 2010)
An overview; The science of psychological measurement; The assessment of intelligence; The assessment of personality; Testing and assessment in action.
Includes bibliographical references
Keywords: Psychological tests -- Problems, exercises, etc; Psychometrics -- Problems, exercises, etc; Tâm lý học